The Feasibility of Taekwondo for Addressing Social Interaction and Social Participation in Children - Mariel Calinog; Julie Kugel; Dragana Krpalek; Arezou Salamat (Scholarworks @ WMU, 2021)
Background: Children with autism spectrum disorder (ASD) often experience physical, social, and emotional barriers that impact participation in extracurricular activities, such as taekwondo. Engaging in taekwondo may provide opportunities for advancing social abilities as well as developing health-promoting behaviors and routines. Therefore, the purpose of this feasibility study was to explore the effectiveness of using a form of martial arts, taekwondo, as an intervention to promote social participation in everyday life. Method: A mixed-methods design was used. Three children between 7 and 8 years of age who met the ASD criteria participated in a 7-week taekwondo program. The children engaged in interviews before and after the program. The parents completed the Autism Social Skills Profile-2 (ASSP-2) and completed pre and post interviews. Results: Four themes emerged from the qualitative data: social interactions, physical abilities, community barriers and supports, and intervention feasibility. Overall, the qualitative data highlighted the children's increased confidence with social interaction, interests in exploring activities, and program satisfaction. Although not statistically significant, the ASSP-2 scores increased for each child after participation in the program. Conclusion: This study suggests that taekwondo may promote self-confidence in social and physical abilities, leisure exploration, and participation in children with social interaction skills deficits.